Analysis of Donald Trump's Speech: Ideological Structure and Rhetorical Strategy - Gomes, Maria Laura Rodrigues; Rosa, André Felipe (Revista Coleta Científica, 2024)
This study carries out an analysis of Donald Trump's political speech, using Discourse Analysis tools and the Iramuteq software, focusing on the theoretical concepts of Michel Pêcheux and Eni Orlandi. The results of the quantitative and qualitative analysis show the use of discursive strategies such as polarization, repetition of key themes and appeal to nationalism to build a collective identity among its supporters. Based on the theories of Pêcheux and Orlandi, the research explores how Trump's speech shapes a worldview that propagates ideologies and aligns with the speaker's political interests.